Biliary tract complications during cholecystectomies in a reference service in Pará (Research, Society and Development, 2022)
Objective: To quantify the cases of iatrogenic lesions of the bile ducts (LIVB) during laparoscopic cholecystectomies (CVL) in the General Surgery Service of Fundação Santa Casa de Misericórdia do Pará (FSCMPA) between 2017 and 2021. This study will be responsible for identifying the factors of risk, incidence and outcome of LIVB. Methodology: An observational, retrospective and descriptive study was carried out, using data from the medical records of patients undergoing SVC at the FSCMPA in the proposed period. Data analysis: It was performed using the BioEstat 5.0 program, the G test was used to compare the categories and the significance value for analysis was less than 5% (5% alpha). Result: A total of 1,118 cholecystectomies were identified, of which 76.11% (n: 851) were female, 13 had some type of bile duct injury, corresponding to 1.16%. Early identification occurred in 38.5% of cases, 30.8% by direct intraoperative observation, by performing intraoperative cholangiography (7.7%), later, with ERCP in 15.4% of cases or cholangio-MRI in 46.1%. The main treatments in the repair of bile duct injuries were: biliodigestive bypass (DBD), ERCP - 15.4%, primary repair with Kehr drain - 15.4%. Final considerations: The data are high compared to other studies, the lesions were more prevalent in females and the most used exam in the diagnosis was the MRI cholangio. Regarding treatment, in most cases DBD was performed.